Strategies for Articular Cartilage Repair and Regeneration - Liu, Yanxi; Shah, Karan M.; Luo, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
Articular cartilage is an avascular tissue, with limited ability to repair and self-renew. Defects in articular cartilage can induce debilitating degenerative joint diseases such as osteoarthritis. Currently, clinical treatments have limited ability to repair, for they often result in the formation of mechanically inferior cartilage. In this review, we discuss the factors that affect cartilage homeostasis and function, and describe the emerging regenerative approaches that are informing the future treatment options.